A Comparison of Wage Determination Methods in the Americas - Jecchinis, Chris; Phillips, Gerald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
This study compares the methods that are used to determine wages in the developing and developed countries of the Americas.